To simplify the expression \( -(2x+6)(3x+4)+5x^2−7x \), we will follow these steps:
- Expand the product: \( -(2x + 6)(3x + 4) \).
- Combine like terms.
Let's go step by step.
Step 1: Expand \( -(2x + 6)(3x + 4) \)
First, we will calculate \( (2x + 6)(3x + 4) \):
\[ (2x + 6)(3x + 4) = 2x \cdot 3x + 2x \cdot 4 + 6 \cdot 3x + 6 \cdot 4 \] \[ = 6x^2 + 8x + 18x + 24 \] \[ = 6x^2 + 26x + 24 \]
Now applying the negative sign:
\[ -(2x + 6)(3x + 4) = - (6x^2 + 26x + 24) = -6x^2 - 26x - 24 \]
Step 2: Combine with \( 5x^2 - 7x \)
Now, we combine this result with \( 5x^2 - 7x \):
\[ -6x^2 - 26x - 24 + 5x^2 - 7x \]
Combining like terms (for \(x^2\) terms and \(x\) terms):
For \(x^2\) terms: \[ -6x^2 + 5x^2 = -x^2 \]
For \(x\) terms: \[ -26x - 7x = -33x \]
Now putting it all together:
\[ -x^2 - 33x - 24 \]
Conclusion
The simplified expression is:
\[ -x^2 - 33x - 24 \]
So the final answer is:
−x²−33x−24